2019
DOI: 10.1029/2018ja026419
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Intraseasonal Variability of Nighttime Ionospheric Irregularities Over Taiwan

Abstract: The nature of intraseasonal (within a season) variability of the nighttime ionospheric irregularities has been studied utilizing the observation of the recently installed VHF scintillation receiver from Pingtung, Taiwan. Investigation is based on observations made in 2015 (high‐moderate solar epoch) and 2017 (low solar epoch). Detailed investigation has revealed coexistence of planetary‐scale variability (3–7 days), 10‐ to 16‐day variability, and > 25‐day variability in 2015. Interestingly, the Lomb‐Scargle fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Further, steep TEC gradients associated with EPBs may also adversely affect the integrity of space-based augmentation systems (SBASs) and ground-based augmentation systems (GBASs) in civil aviation (see, e.g., Yoon et al, 2017). The occurrence of EPBs follows a regular seasonality (Burke et al, 2004;Gentile et al, 2006aGentile et al, , 2006b, but there is significant day-to-day variability in EPB occurrence as well (Ogawa et al, 2006(Ogawa et al, , 2009Joshi et al, 2019), which is far more difficult to forecast (e.g., Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further, steep TEC gradients associated with EPBs may also adversely affect the integrity of space-based augmentation systems (SBASs) and ground-based augmentation systems (GBASs) in civil aviation (see, e.g., Yoon et al, 2017). The occurrence of EPBs follows a regular seasonality (Burke et al, 2004;Gentile et al, 2006aGentile et al, , 2006b, but there is significant day-to-day variability in EPB occurrence as well (Ogawa et al, 2006(Ogawa et al, , 2009Joshi et al, 2019), which is far more difficult to forecast (e.g., Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the Indian sub-continent, Goswami et al (2017) found intense scintillations at the northern anomaly crest region of Calcutta during the equinoxes and Joshi et al (2019) found that scintillation variability in the autumnal equinox was highly correlated with the periodic geomagnetic activity. Sahithi et al (2019) investigated the climatology of scintillations over India at stations located around the crest and trough regions of the EIA, identifying that the probability of scintillations is higher during March equinox and December solstice, and lowest during June solstice, maximizing in the post-sunset hours.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction/forecast of EPB is considered vital as it can adversely affect the accuracy and continuity of the satellite based navigation. Intermediate scale irregularities present inside the EPB scatters the radio waves transmitted by the navigation satellites in forward direction which can result in the rapid fluctuation of the signal amplitude and phase on ground (de Lima et al, 2015;Joshi et al, 2019a;Joshi et al, 2019b;Kintner et al, 2004;Ledvina et al, 2004;Retterer, 2010;Rezende et al, 2010). Such rapid fluctuations are termed ionospheric scintillations, which can result in the signal outage and/or loss of the receiver lock on the signal.…”
Section: Introductionmentioning
confidence: 99%